Simplified Design Procedure for RC Ribbed Slabs in Fire Based on Experimental and Numerical Thermal Analysis - Fabrício Longhi Bolina; Arthur S. Henn; Bruno Dal Lago (Buildings)
Ribbed slabs are a solution for increasing the bending capacity while reducing the total concrete consumption and the dead weight compared to conventional reinforced concrete slabs. The EN 1992-1.2 standard contains a tabulated method (TM) for the fire design of these structures, which suggests combinations of cross-sectional dimensions and concrete cover thickness to determine the fire resistance. Using a finite element (FE) model solved with Abaqus software, a transient thermal analysis of these slabs was performed, correlating the results with the standardized TM. Cross-sections with different concrete widths and concrete covers were numerically tested to define a new TM based on the same criteria proposed by the EN. To validate the FE models, the results were compared with the experimental data of two full-scale specimens of ribbed slabs. It was found that the current TM is not consistent in all cases, and the concrete cover needs to be improved by between 20 and 50%. A fire design of ribbed slabs based on EN 1992-1.2 shows that the reinforcement is heated beyond its critical temperature, but the flange thickness can be reduced. A new tabular procedure is proposed based on the critical temperature of the reinforcement, the concrete cross-section, and the thermal insulation criteria.